Hate crimes : when intolerance turns violent - Sharif, Meghan (Hot topics (Lucent Press), 2018)
Overviews a number of high-profile hate crimes committed in recent history in the United States, profiling perpetrators and organized hate groups--such as the KKK--and discusses why hate crimes get committed and what readers can do to help stop them from happening.